Use of rpoB Gene Analysis for Detection and Identification of Bartonella Species - Renesto, Patricia (American Society for Microbiology, 2001)
Identification of Bartonella species is of increasing importance as the number of infections in which these bacteria are involved increases. To date, these gram-negative bacilli have been identified by various serological, biochemical, and genotypic methods. However, the development of alternative tools is required, principally to circumvent a major risk of contamination during sample manipulation. The aim of our study was to investigate the possible identification of various Bartonella species by comparison of RNA polymerase beta-subunit gene (rpoB) sequences. This approach has previously been shown to be useful for the identification of members of the family Enterobacteriaceae (C. M. Mollet, M. Drancourt, and D. Raoult, Mol. Microbiol. 26:1005–1011, 1997). Following PCR amplification with specific oligonucleotides, a 825-bp region of the rpoB gene was sequenced from 13 distinct Bartonella strains. Analysis of these sequences allowed selection of three restriction enzymes (ApoI, AluI, and AflIII) useful for discerning the different strains by PCR-restriction fragment length polymorphism (PCR-RFLP) analysis. To confirm the potential value of such an approach for identification of Bartonella, the rpoB PCR was then applied to 94 clinical samples, and the results obtained were identical to those obtained by our reference PCR method. Twenty-four isolates were also adequately identified by PCR-RFLP analysis. In all cases, our results were in accordance with those of the reference method. Moreover, conserved regions of DNA were chosen as suitable primer targets for PCR amplification of a 439-bp fragment which can be easily sequenced.